2014
DOI: 10.1111/iju.12413
|View full text |Cite
|
Sign up to set email alerts
|

Role of male pelvic floor muscles and anterior fibromuscular stroma in males on α1‐blocker treatment: A magnetic resonance imaging study

Abstract: Abbreviations & AcronymsAbstract: Dynamic motion of the pelvic floor muscles during voiding was analyzed using real-time magnetic resonance imaging. To evaluate the contraction of the pelvic floor muscles, striated urethral sphincter distance, levator ani muscle thickness and anterior fibromuscular stroma distance were measured. The percent contraction of the striated urethral sphincter from before voiding to just before initiation of voiding was 14% in the normal group and 5% in the voiding dysfunction group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…I believe this theory of relaxation of the AFMS fits with the understood physiology of micturition, and could explain what Nishio and others observed during voiding . This study is intriguing, and raises some interesting questions regarding the role of the AFMS in health and disease.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…I believe this theory of relaxation of the AFMS fits with the understood physiology of micturition, and could explain what Nishio and others observed during voiding . This study is intriguing, and raises some interesting questions regarding the role of the AFMS in health and disease.…”
supporting
confidence: 67%
“…The prevailing hypothesis views the prostate as a static organ with a constant smooth muscle tone, though this has been challenged by Nishio et al . Data obtained by real time magnetic resonance imaging clearly shows that the prostate is dynamic, and an active participant in the voiding process. Analyses of healthy volunteers have shown that the anterior prostate shortens during voiding, causing a mean reduction of 5–8 mm in the distance measured from the bladder neck to the prostatic apex.…”
mentioning
confidence: 99%
“…Shortening of the AFMS (on the craniocaudal plane) is required before initiation of voiding and this shortening was found to be more prominent in patients with normal voiding when compared to patients with voiding dysfunction . In the real‐time MRI studies of Hocaoglu et al, the AFMS distance was found to be less during voiding than that before voiding.…”
Section: Discussionmentioning
confidence: 97%
“…The craniocaudal distance of the ventral prostate from the internal urethral orifice to the prostate apex was defined as anterior fibromuscular stroma (AFMS) distance and determined on sagittal T 2 ‐weighted MR images (Fig. B) . Prostatic urethral angle (PUA) was determined on sagittal T 2 ‐weighted MR images by measuring the acute angle between the proximal prostatic urethra and the distal prostatic urethra, similar to the method described previously (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The total score is the sum of the seven questions ranging from 0 to 35. The patients are classified according to IPSS score into three groups: mild, 0-7; moderate, [8][9][10][11][12][13][14][15][16][17][18][19]; and severe, 20-35 [1,2].…”
Section: Introductionmentioning
confidence: 99%